2013
DOI: 10.1016/j.fluid.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

A new microebulliometer for the measurement of the vapor–liquid equilibrium of ionic liquid systems

Abstract: Over the last decade ionic liquids appeared as potential entrainers for extractive distillation processes. However experimental vapor-liquid equilibrium data for ionic liquid containing systems is still scarce since most conventional equilibrium cells are not adequate for these systems. To overcome that limitation a new isobaric microebulliometer, operating at pressures ranging from 0.05 to 0.1 MPa and requiring a sample volume lower than 8 mL was developed and validated in this work. The new apparatus was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 21 publications
(36 reference statements)
3
51
0
Order By: Relevance
“…Its non-flammability, non-volatility, good thermal and radiation stability makes them an excellent alternative for conventional and volatile organic solvents used in industrial and academic research work [5][6][7][8][9][10][11]. Adding to this, IL can dissolve almost every organic and inorganic species, for example, elements (like Phosphorus, Sulphur etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Its non-flammability, non-volatility, good thermal and radiation stability makes them an excellent alternative for conventional and volatile organic solvents used in industrial and academic research work [5][6][7][8][9][10][11]. Adding to this, IL can dissolve almost every organic and inorganic species, for example, elements (like Phosphorus, Sulphur etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of such interactions can be derived from physico-chemical measurements such as solubilities [7,8], activity coefficients of solutes at infinite dilution ( ∞ 13 γ ) [9][10][11][12], molecular simulation [13,14], spectroscopic techniques [15][16][17], vapor-liquid equilibrium (VLE) data [18,19] and liquid-liquid equilibrium (LLE) data [20,21], as well as from thermodynamic models such as equations of state [22] or from COSMO [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Not only the available equipments, developed for conventional solvents, require a large sample volume ranging from the 250 cm 3 of Wang et al [36] down to the recently reported used of a glass Fischer Labodest equilibrium still that requires a sample volume of circa 35 cm 3 [37][38][39][40][41][42][43]. Moreover the high viscosity of the mixtures rich in ionic liquid difficult a regular boiling of the mixture, what causes long equilibration times, easily reaching 6 h. To overcome these limitations we have recently reported a microebulliometer of just 8 cm 3 of capacity to study these systems [44]. The ebulliometer measurements remain, however, a difficult and very time consuming task so with aim at developing an experimental technique that would provide a fast, reliable and cheap scan of ionic liquids, and their interaction with water, the measurement of water activities using a hygrometer is proposed.…”
Section: Introductionmentioning
confidence: 99%